MODIFIKASI OTOMATISASI VALVE AIRFLOW MESINPRESS AIDA NC1 350 PADA PROSES PRODUKSI DISCBRAKE SEPEDA MOTOR - Farras Agung Nugroho, (2020)
Development of the production process of an item begins with the use of human labor until now it has used various kinds of machines as its main process. Manufacturing process using a machine has a series of grooves throughout the process so that it can be said in terms of the machining process. Machining process using a base metal cutting is divided into the process of cutting by means of press, traditional cutting with simple tools, as well as non-conventional cutting. Press machines used to cut production materials often experience various kinds of damage and failures during the production process. One of the most common damages found on a press machine is a reversed flower groove, a disc disk chamber that has a disposition, an incorrect setting of the blade, and an overhaul of the flywheel bearing that is often troubled. Air flow or better known as airflow is produced by a compressor engine so that it can channel compressed air to various kinds of production machines through a sealing valve. Factors affecting valve leakage are due to operator error that is not in accordance with the procedure. So the solution for valve leakage is to replace conventional valves with selenoid automatic valves.